Bacteremic Urinary Tract Infection Caused by Multidrug-Resistant Enterobacteriaceae Are Associated With Severe Sepsis at Admission: Implication for Empirical Therapy. Issue 20 (May 2016) - Lee, Yi-Chien; Hsiao, Chih-Yen; Hung, Miao-Chiu; Hung, Sheng-Che; Wang, Hung-Ping; Huang, Yun-Jhong; Wang, Jann-Tay
Abstract : Abstract: The purpose of this study is to compare the clinical features and treatment outcomes among patients with bacteremic urinary tract infection (UTI) caused by multidrug-resistant (MDR) and non-MDR Enterobacteriaceae and to identify whether MDR pathogens were independently associated with severe sepsis or septic shock at presentation. The clinical data of adult patients visiting and being treated at Chia-Yi Christian Hospital due to bacteremic UTI caused by Enterobacteriaceae from January 2006 to August 2015 were retrospectively analyzed. A total of 585 patients were enrolled. Among them, 220 (37.6%) were caused by the MDR Enterobacteriaceae . A total of 206 patients (35.2%) developed severe sepsis or septic shock at presentation. Patients in the MDR group tend to be male and have a past history of gout, recurrent UTI, prior hospitalization, hydronephrosis, renal stone, ureteral stone, indwelling urinary catheter, newly development of renal dysfunction, severe sepsis or septic shock, intensive care unit (ICU) admission, receipt of ineffective empirical therapy, longer hospital stay, and higher in-hospital mortality (2.7% vs 1.9%, P  = 0.569). Using multivariate logistic regression analysis, it is revealed that independent predictors associated with severe sepsis or septic shock at presentation were liver cirrhosis (OR 2.868; 95% CI 1.439–5.716; P  = 0.003), indwelling urinary catheter (OR 1.936; 95% CI 1.238–3.027; P  = 0.004), and MDR Enterobacteriaceae (OR 1.447; 95% CI 1.002–2.090; P  = 0.049). Multidrug resistance was associated with the development of severe sepsis or septic shock upon presentation among patients with bacteremic UTI caused by Enterobacteriaceae. Therefore, empirical antibiotics therapy for patients with UTI presented with severe sepsis and/or septic shock should be more broad-spectrum to effectively cover MDR Enterobacteriaceae.